STUDIES ON THE BETA CELLS OF ISLETS OF LANGERHANS OF ALLOXAN INDUCED DIABETIC ALBINO RATS TREATED WITH ALCOHOLIC SEED EXTRACT OF CAESALPINIA BONDUCELLA - SAGAR , VEDAVYASA; AHAMED, R. NAZEER (The Bioscan, 2014)
Present investigation was undertaken to evaluate the potential anti-diabetic activity of alcoholic seed extract of Caesalpinia bonducella (ASECB) on Islets of albino rats. The rats were divided into four groups, Control, Diabetic control, Diabetic + 200 mg ASECB and Diabetic + 400 mg ASECB. Oral administration of different doses of ASECB to diabetic rats was conducted for a period of 14 days. Blood glucose level was estimated on 0, 3rd, 10th and 17th day. Histopathology of the pancreas and marphometry of beta cells was studied. The body weight of the diabetic control rats was significantly reduced. The body weight was regained and there was significant increase in the final body weight in treated groups. Treated animals showed a significant decrease in blood glucose level. The number of beta cells in diabetic rats compared to controls was significantly reduced. Treated rats showed significant increase in number of beta cells. The islet size in diabetic group significantly decreased when compared to control. The animals treated with ASECB showed a significant increase in islet size. Thus, it is suggested ASECB could serve as a good oral hypoglycemic agent.